1998
DOI: 10.1111/j.1469-7793.1998.527bn.x
|View full text |Cite
|
Sign up to set email alerts
|

Multiple pathways for L‐methionine transport in brush‐border membrane vesicles from chicken jejunum

Abstract: The intestinal transport of L‐methionine has been investigated in brush‐border membrane vesicles isolated from the jejunum of 6‐week‐old chickens. L‐Methionine influx is mediated by passive diffusion and by Na+‐dependent and Na+‐independent carrier‐mediated mechanisms. In the absence of Na+, cis‐inhibition experiments with neutral and cationic amino acids indicate that two transport components are involved in L‐methionine influx: one sensitive to L‐lysine and the other sensitive to 2‐aminobicyclo[2.2.1]heptane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
19
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Although the expression of system y ϩ in epithelial cells has often been restricted to the basolateral membrane (6,20), Thwaites et al (46) reported the participation of this transport mechanism in L-Lys transport across the apical membrane of Caco-2 cells. In addition, we have previously found a Na ϩ -independent L-Met component sensitive to NEM, a specific inhibitor of system y ϩ (11), in chicken brush-border membrane vesicles (40). Those results not only confirmed y ϩ activity in the apical membrane but also indicated the capacity of this mechanism to transport L-Met in the absence of Na ϩ .…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…Although the expression of system y ϩ in epithelial cells has often been restricted to the basolateral membrane (6,20), Thwaites et al (46) reported the participation of this transport mechanism in L-Lys transport across the apical membrane of Caco-2 cells. In addition, we have previously found a Na ϩ -independent L-Met component sensitive to NEM, a specific inhibitor of system y ϩ (11), in chicken brush-border membrane vesicles (40). Those results not only confirmed y ϩ activity in the apical membrane but also indicated the capacity of this mechanism to transport L-Met in the absence of Na ϩ .…”
Section: Discussionsupporting
confidence: 67%
“…Both isoforms are expressed in Caco-2 cells (13), but some authors report the restriction of their expression to the basolateral membrane in the intestinal epithelium (50). Nevertheless, a Na ϩ -independent transport component for neutral amino acids sensitive to BCH has been detected in the apical membrane of chicken, pig, and rabbit intestine (22,40,42). Moreover, Berger et al (1) reported that apical Na ϩ -independent L-phenylalanine uptake was mediated by systems b 0,ϩ and L in Caco-2 cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether these groups of poly(A) ϩ RNA encode the same transport protein or different proteins is unclear at this moment. Using brush border membrane vesicles as the model, Soriano-Garcia et al (7,17) reported that Met is transported in the chicken jejunum by four transport systems: system b 0,ϩ -like, y ϩ m-like, L-like, and B-like. How these four transport systems relate to the current results has yet to be determined.…”
Section: Resultsmentioning
confidence: 99%
“…For years, several models have been employed in attempts to reveal the absorption mechanisms for Met and/or HMB in chickens (1)(2)(3)(4)(5)(6)(7). These studies suggested that mechanisms of methionine absorption included Na ϩ -dependent transport, Na ϩ -independent transport and/or diffusion.…”
mentioning
confidence: 99%